Specific Human ATR and ATM Inhibitors Modulate Single Strand DNA Formation in Leishmania major Exposed to Oxidative Agent - da Silva, Raíssa Bernardes; Bertoldo, Willian dos Reis; Naves, Lucila Langoni; de Vito, Fernanda Bernadelli; Damasceno, Jeziel Dener; Tosi, Luiz Ricardo Orsini; Machado, Carlos Renato; Pedrosa, André Luiz (Frontiers in Cellular and Infection Microbiology, 2022)
Leishmania parasites are the causative agents of a group of neglected tropical diseases named leishmaniasis. The molecular mechanisms employed by these parasites in order to adapt to the adverse conditions found in their hosts are not completely understood. One of such processes consists in gene amplification, which reflects the high tolerance of these parasites to significant genome modifications. DNA repair pathways could be used by Leishmania to enable these processes. In higher eukaryotes, these pathways are coordinated by the central protein kinases Ataxia Telangiectasia Mutated (ATM) and Ataxia Telangiectasia and Rad3 related (ATR). The enzyme Exonuclease-1 (EXO1) plays important roles in DNA replication, repair and recombination, and it could be regulated by ATM- and ATR-mediated signaling pathways. The present work aimed to investigate these DNA damage response pathways in promastigote forms of L. major using bioinformatics tools, exposure of lineages to oxidizing agent and radiation damage, treatment of cells with ATM and ATR inhibitors and flow cytometry analysis. We demonstrated the high structural and important residues conservation for the catalytic activity of putative LmjEXO1. The overexpression of putative LmjEXO1 renders L. major cells more susceptible to genotoxic damage, probably due to the nucleasic activity of this enzyme and the occurrence of hyper-resection of DNA strands. These cells could be rescued by the addition of caffeine or selective ATM inhibitor. In contrast, ATR specific inhibition turn control cells more susceptible to oxidative damage, in an LmjEXO1 overexpression-like manner. We demonstrated that ATR specific inhibition leads to formation of extended single strand DNA, probably due to EXO1 nucleasic activity. Antagonistically, ATM inhibition prevented the single strand DNA formation, which could explain the surviving phenotype of lineages overexpressing LmjEXO1. These results suggest that an ATM homologue in Leishmania could act promoting end resection by putative LmjEXO1, and an ATR homologue could prevent hyper-resection, ensuring an adequate repair of the parasite DNA.